UPIA KARANJI HOME INDUSTRY BUSINESS MANAGEMENT (KOPIAH BASKET) IN POLOHUNGO VILLAGE - Sindri Ibrahim; Samin Latif; Fibriyanti Lakoro (Journal of Economic, Business, and Administration (JEBA), 2022)
The purpose of this research is to find out the problems faced by the home industry business in Polohungo Village and to find out how they carry out promotional and marketing activities. In this study, the researcher used a descriptive type of research with a qualitative approach. The research instrument is the key instrument or the main instrument. Data was obtained by using data collection techniques in the form of observation, interviews, and documentation. For further processing using qualitative data analysis techniques that were carried out interactively. The results of the study concluded that Upia Karanji's Home Industry Business Management (Kopiah Basket) includes planning, organizing, actuating, and controlling.